2018
DOI: 10.1021/acs.est.8b00700
|View full text |Cite
|
Sign up to set email alerts
|

Multigenerational Disruption of the Thyroid Endocrine System in Marine Medaka after a Life-Cycle Exposure to Perfluorobutanesulfonate

Abstract: Accumulation of perfluorobutanesulfonate (PFBS) is frequently detected in biota, raising concerns about its ecological safety. However, hazardous effects of PFBS remain largely unexplored, especially for endocrine disrupting potency. In the present study, the multigenerational endocrine disrupting potential of PFBS was investigated by exposing F0 marine medaka eggs to PFBS at different concentrations (0, 1.0, 2.9, and 9.5 μg/L) until sexual maturity. The F1 and F2 generations were reared without continued expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…In this regard, a systematic evidence map has been recently utilized by Pelch et al to summarize the available scientific evidence from in vitro, in vivo, as well as epidemiological studies related to 29 individual PFAS substances of concern for health effects on humans and biota (97), which is publicly available (98). Apart from legacy PFAS, such as PFOS and PFOA, whose endocrine disruptive effects are well recognized, the data suggest that short-chain alternatives such as PFBS, PFHxS, PFTrDA and GenX can affect hormone activities and physiology in non-occupationally exposed humans and other living organisms (99)(100)(101)(102). Another longitudinal study on a Danish birth cohort, investigating potential effects of different PFAS on pubertal development, reported that prenatal exposure to PFOS, PFNA, PFDA, PFHxS and PFHpS, was associated with an earlier onset of typical puberty indicators in girls, an effect that was also present in boys, although limited to PFHxS and PFHpS.…”
Section: Pfas Impacts On the Endocrine System And Biological Mechanismsmentioning
confidence: 99%
“…In this regard, a systematic evidence map has been recently utilized by Pelch et al to summarize the available scientific evidence from in vitro, in vivo, as well as epidemiological studies related to 29 individual PFAS substances of concern for health effects on humans and biota (97), which is publicly available (98). Apart from legacy PFAS, such as PFOS and PFOA, whose endocrine disruptive effects are well recognized, the data suggest that short-chain alternatives such as PFBS, PFHxS, PFTrDA and GenX can affect hormone activities and physiology in non-occupationally exposed humans and other living organisms (99)(100)(101)(102). Another longitudinal study on a Danish birth cohort, investigating potential effects of different PFAS on pubertal development, reported that prenatal exposure to PFOS, PFNA, PFDA, PFHxS and PFHpS, was associated with an earlier onset of typical puberty indicators in girls, an effect that was also present in boys, although limited to PFHxS and PFHpS.…”
Section: Pfas Impacts On the Endocrine System And Biological Mechanismsmentioning
confidence: 99%
“…A resultant shift in the reproductive cycle may ultimately affect population size and diversity. For example, delayed hatching has been described in marine medaka Oryzias melastigma (McClelland, 1839) (and offspring) following exposure to the surfactant perfluorobutanesulfonate, primarily as a result of disruption to the thyroid system (Chen et al, 2018). Other population-level effects are reviewed by Marty et al (2017) and some are discussed later in this review.…”
Section: Fishmentioning
confidence: 99%
“…In contrast to amphibian assays, TH content in eggs, whole-body larvae or even circulating levels in adults (Chen et al, 2018;Wei et al, 2018;Yu et al, 2014) have routinely been measured in teleosts (50 out of 73) ecotoxicological studies retrieved). Additionally, a particular vulnerable time windows to THADCs such as the transition from the embryonic to larval stage occurs relatively rapidly, i.e.…”
Section: Endpoints In Fish Models For Identification Of Thyroid Disrumentioning
confidence: 99%
“…only 2-3 dpf in zebrafish (Walter et al, 2019), and metamorphosis (larva-to-juvenile transition) initiates after 2 weeks (Sharma et al, 2016). The subsequent generation may be obtained in 2-4 months to provide evidence of transgenerational effects following THADC exposure, whilst also having the advantage of taking into account gender-specific effects (Chen et al, 2018;Cheng et al, 2017;Han et al, 2017;Jianjie et al, 2016;Wang et al, 2015;Yu et al, 2014;Zhao et al, 2016). These features represent outstanding advantages for addressing the long-term effects (into adulthood and on offspring) of EDCs which is more pertinent to real life exposure scenarios consisting of chronic exposure to low doses of environmental chemicals, and invaluable for potential studies on heritable EDC-induced epigenetic alterations of gene expression (Alavian- Ghavanini and Rüegg, 2018;Baker et al, 2014).…”
Section: Endpoints In Fish Models For Identification Of Thyroid Disrumentioning
confidence: 99%